Synthesis and spectroscopic study of highly fluorescent carbon dots derived from orange juice with Stilbene 420 dye - Mahmood, Yazan Abdulmuttaleb; Chiad, Bahaa T. (Iraqi Journal of Physics, 2020)
Highly-fluorescent Carbon Quantum Dots (CQDs) are synthesized in simple step by hydrothermal carbonization method of natural precursor such as orange juice as a carbon source. Hydrothermal method for synthesized CQDs requires simple and inexpensive equipment and raw materials, thus this method are now common synthesis method. The prepared CQDs have ultrafine size up to few nanometers and   several features such as high solubility in water, low toxicity, high biocompatibility, photo-bleaching resistant, Chemical inertness and ease of functionalization which qualifies it for use in many applications such as bio-imaging, photo-labeling and photo-catalysis.       This research demonstrates the method of prepared highly fluorescence CQDs and also briefly introduce the most commonly used techniques for characterizing CQDs and the results obtained and studying their optical properties by adding Stilbene 420 dye in a method that changes the input power of used laser and prove that the output power intensity depends on the input power.